The Impact of Learning Motivation, Self-Efficacy, and Academic Procrastination on Economics Achievement - Julita Marlina Miftahul Jannah; Jun Surjanti (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
Students’ low achievement in economics has become a major concern and is presumed to be influenced by psychological factors, to be specific learning motivation, self-efficacy, and academic procrastination behavior. This study aims to examine the effects of these three variables on students’ economics learning outcomes. A quantitative approach with a causal research design was employed. The sample consisted of 206 tenth-grade students of SMAN 4 Sidoarjo selected through simple random sampling. Data were collected using questionnaires and documentation, and subsequently analyzed with SPSS through multiple linier regression analysis. The finding reveal that learning motivation and self-efficacy have positive and statistically significant effect on economics learning outcomes, while academic procrastination shows a negative and significant effect. Simultaneously, the three variables significantly influence learning outcomes and account for 25,2% of the variance, whereas the remaining 74,8% is explained by other factors beyond the research model. The result highlight the importance of strengthening students’ learning motivation and self-efficacy, as well as minimizing academic procrastination through effective instructional strategies. This study is limited to the variables examined and to a single school setting, therefore, future research is recommended to incorporate additional variables and involve broader research site to obtain more comprehensive findings